Case report: Reconstruction with thyrohyoidopexy in a dog presented with complete laryngo-tracheal separation - Dos-Santos, José Diogo; Belo, Luís; Monteiro, Mariana; Mestrinho, Lisa A. (Frontiers in Veterinary Science, 2025)
A 2-year-old Norfolk Terrier purebred female dog was presented for urgent attention after strangulation secondary to elevator entrapment. The traumatic event caused a complex laryngopharyngeal lesion with total laryngotracheal and esophageal separation from the hyoid bone and pharynx. Reconstruction was performed from the posterior pharyngeal wall, and all layers, mucosa, muscles and ligaments were repaired. A thyrohyoidopexy was done using nonabsorbable sutures to reinforce the thyrohyoid membrane reconstruction and prevent reseparation in the immediate postoperative period. The patient's fully recovery was gradual but uneventful, with occasional cough resolving within 2 months.